Assessment of genetic divergence in pumpkin (Cucurbita moschata) - Neha; Ajeet Singh; Manish Kumar Singh; Himanshu Singh; Jayshree Singh; Varun Dwivedi; S.V. Dwivedi (Current Horticulture, 2025)
Eighteen diverse genotypes of pumpkins (Cucurbita moschata Duch expoiq.) were evaluated for phenotypical variations and assessment of genetic diversity during the kharif season 2022 at Vegetable Research Farm, Banda University of Agriculture and Technology, Banda, Uttar-Pradesh. Randomized Complete Block Design with three replications was used for divergence, 18 genotypes were grouped into 4 clusters using Tocher’s method. Out of the 6 clusters, cluster I was the largest, comprising 8 genotypes, followed by cluster III, comprising 5 genotypes, cluster IV, 4 genotypes, and cluster II with 1 genotype only. Based on distances between clusters, i.e. inter-cluster distances, maximum divergence was observed between cluster III and cluster IV. Maximum inter-cluster D2 values between clusters indicated that genotypes included in these clusters can be used as a parent in hybridization programme to get higher heterotic hybrids from the segregating population. The maximum intra-cluster D2 values were observed for cluster I. Maximum intra-cluster distance indicates that genotypes are very diverse. Presence of sufficient phenotypic and genotypic diversity showed the scope in pumpkin for further improvement.